2017
DOI: 10.1111/1748-5967.12259
|View full text |Cite
|
Sign up to set email alerts
|

Novel antibacterial peptides induced by probiotics in Hermetia illucens (Diptera: Stratiomyidae) larvae

Abstract: There is a need to discover new therapeutic substances due to the emergence of deadly infectious diseases and various antibiotic resistance. We focused on the larvae that are utilized as a medical insect for the treatment of skin damage in Europe and America. This study was to investigate the pharmacological activities of novel antibacterial peptides isolated from Hermetia illucens larvae against the Klebsiella pneumoniae and Shigella dysenteriae. The larvae were immunized by probiotics (Lactobacillus casei) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 47 publications
1
21
2
Order By: Relevance
“…Hemolymph from BSFL immunized with Lactobacillus casei (probiotic) were fractionated to identify specific peptides responsible for antibacterial activity and the fraction HP/F9 (screened by high-performance liquid chromatography (HPLC)) with inhibitory effects on the growth of bacteria was tested for in vitro cytotoxicity. The peptides did not exhibit a significant level of cytotoxicity; the results support the fact that BSFL can be used to produce AMP with unique properties, pharmacological action and complete cytocompatibility on bacteria and cells [124]. A novel cecropin-like peptide with a molecular weight of 4.84 kDa was isolated from BSFL and characterized.…”
Section: Functional and Bioactive Peptidessupporting
confidence: 58%
“…Hemolymph from BSFL immunized with Lactobacillus casei (probiotic) were fractionated to identify specific peptides responsible for antibacterial activity and the fraction HP/F9 (screened by high-performance liquid chromatography (HPLC)) with inhibitory effects on the growth of bacteria was tested for in vitro cytotoxicity. The peptides did not exhibit a significant level of cytotoxicity; the results support the fact that BSFL can be used to produce AMP with unique properties, pharmacological action and complete cytocompatibility on bacteria and cells [124]. A novel cecropin-like peptide with a molecular weight of 4.84 kDa was isolated from BSFL and characterized.…”
Section: Functional and Bioactive Peptidessupporting
confidence: 58%
“…In a previous study, we reported that L. casei injection activated the immune system in HIL and induced AMP expression [ 23 ]. Therefore, we developed an AMIS using fine needles to inject HIL with L. casei in quantity ( Figure 1 A,D).…”
Section: Resultsmentioning
confidence: 99%
“…However, to trigger the mass production of AMPs, pathogens must be introduced into the body cavity because AMP expressions are up-regulated only after activation of the innate immune system [ 20 , 21 ]. In a previous study, we found that the antimicrobial activities of H. illucens larvae (HIL) extract and hemolymph were enhanced by infection with human or animal pathogens [ 22 ], and interestingly, Chol et al reported that probiotics induce AMPs in HIL [ 23 ]. Here, we developed an automatic mass injection system (AMIS) to establish a means of producing an extract of infected H. illucens larvae (iHIL-E), and then evaluated the antimicrobial activities of iHIL-E against antibiotic- and AMP-resistant bacteria and pathogens, such as Salmonella species, and against Lactobacillus species.…”
Section: Introductionmentioning
confidence: 99%
“…However, H. illucens expresses/secretes AMPs in quantity only after innate immune system activation by a pathogen [ 20 , 21 ]. Choi et al previously demonstrated the antibiotic activity of purified peptide extract in hemolymph isolated from H. illucens larvae (HIL) immunized by Lactobacillus casei against Klebsiella pneumoniae (ATCC 13883) and Shigella dysenteriae (ATCC 9750) [ 22 ]. Here, to select an optimal AMPs inducer, we evaluated antimicrobial activity of HIL immunized with five Lactobacillus species and assessed the bactericidal activities of an extract of HIL immunized with a selected Lactobacillus species to determine the potential use of the extract as a natural antibiotic or preservative.…”
Section: Introductionmentioning
confidence: 99%